(untitled) (Iraqi Journal of Medical Sciences, 2016)
Background: Tacrolimus is an immunosuppressive agent used topically, it has been found to be effective in treating moderate to severe atopic dermatitis without causing the atrophy that might occur with prolonged use of topical corticosteroids. There is a lack of studies on the effect of tacrolimus and steroid Therapy on CCR3 and CCR5 in atopic dermatitis patients. Objective:To assess expression of some chemokine receptors in the epidermis of atopic skin (chronic lesions) and to evaluate any differences in the degree and pattern of epidermal expression before and after topical tacrolimus or steroid therapy. Methods: Twenty five cases of atopic dermatitis before and after treatment by tacrolimus ointment and topical steroids were evaluated immunohistochemically for the epidermal expression pattern and intensity of some chemokine receptors namely CCR3 and CCR5 before and after treatment. Result: CCR5 and CCR3 positive epidermal cells seem to be produced in situ in higher amount before treatment compared with that after treatment. Although these cells are predominantly CCR5+. Conclusions:Enhanced expression of CCR3 and CCR5 on the surface of epidermal keratinocytes may be significant for the determination of atopic reactivity in general and also observed differences in frequencies of these activation markers before and after treatment by topical steroids-tacrolimus therapy. Key words: Atopic dermatitis, CCR3, CCR5, Immunohistochemistry, Tacrolimus